2021
DOI: 10.1021/acsami.1c04961
|View full text |Cite
|
Sign up to set email alerts
|

Operando Reflectance Microscopy on Polycrystalline Surfaces in Thermal Catalysis, Electrocatalysis, and Corrosion

Abstract: We have developed a microscope with a spatial resolution of 5 μm, which can be used to image the two-dimensional surface optical reflectance (2D-SOR) of polycrystalline samples in operando conditions. Within the field of surface science, operando tools that give information about the surface structure or chemistry of a sample under realistic experimental conditions have proven to be very valuable to understand the intrinsic reaction mechanisms in thermal catalysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…2D-SOR data as shown in Figure confirms that the reflectivity decreases radially starting from the sample center. We have previously shown that such a small decrease of the reflectivity coincides with oxide formation. , The formation of an oxide in similar conditions has also been described in the literature. , It is thus likely that oxide formation is driven by the local gas conditions present at ignition. An argument as to why the reflectance difference is not due to a temperature dependency is provided in the SI.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…2D-SOR data as shown in Figure confirms that the reflectivity decreases radially starting from the sample center. We have previously shown that such a small decrease of the reflectivity coincides with oxide formation. , The formation of an oxide in similar conditions has also been described in the literature. , It is thus likely that oxide formation is driven by the local gas conditions present at ignition. An argument as to why the reflectance difference is not due to a temperature dependency is provided in the SI.…”
Section: Discussionsupporting
confidence: 78%
“…We have previously shown that such a small decrease of the reflectivity coincides with oxide formation. 24,28 The formation of an oxide in similar conditions has also been described in the literature. 3,29 It is thus likely that oxide formation is driven by the local gas conditions present at ignition.…”
Section: ■ Discussionmentioning
confidence: 56%
“…In probing gas/surface interactions, surface-sensitive probes such as X-ray photoelectron spectroscopy (XPS) have been, for some time, a critical tool for understanding heterogeneous catalysis reaction mechanisms and for optimizing catalyst activity and selectivity. The corresponding studies at the electrolyte/solid interface are, however, a still-developing area of research. With respect to vanadium oxynitrides, recent ex situ photoemission studies on vanadium nitride nanoparticles have shown that vanadium oxynitrides formed in situ are the active species and that an N surface state with an N 1s binding energy of 396.5 eV is associated with NRR activity. Moreover, the relative photoemission intensity of this feature correlated with the NRR activity of the nanoparticle .…”
Section: Introductionmentioning
confidence: 99%
“…3). [18] Identical colocalization of reflectivity images with electron backscatter diffraction (EBSD) analysis provided a direct correlation of activity from RM with crystallographic orientation. The reflectance voltammograms showed that the step atoms on Au interface ((110) and (111) steps on (210), ( 111) and ( 221) surfaces) are less stable during electrooxidation and oxidize at lower potentials than (111) terrace atoms.…”
Section: Conversion Of Surface Filmsmentioning
confidence: 99%
“…[12] Details on the operational principles of particular RM setups can be found elsewhere. [13,[16][17][18] Standalone, RM provides wide field (up to a few mm wide) highly resolved (down to ca. 200 nm) and sensitive (down to 30 nm particles) measurements while also being amenable to coupling with another methods.…”
Section: Introductionmentioning
confidence: 99%